If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6+3(1-8k)=27
We simplify the equation to the form, which is simple to understand
-6+3(1-8k)=27
Reorder the terms in parentheses
-6+(+3-24k)=27
Remove unnecessary parentheses
-6+3-24k=+27
We move all terms containing k to the left and all other terms to the right.
-24k=+27+6-3
We simplify left and right side of the equation.
-24k=+30
We divide both sides of the equation by -24 to get k.
k=-1.25
| -22=2-3r+7r | | 5(3x-6)=10 | | -0.5s=-28 | | 198=g+12 | | 42=-2(v-8) | | 7+0=x | | -21=9d-7d | | 220=g+70 | | 5(c-6)c+11=24 | | -12=6(x+7) | | 7+y+12y=7 | | -8n+2=-3n-3 | | -5p-24=21(-1+3p) | | b+3-9=29 | | 4(-3+v)=36 | | f(5)=4x-3 | | -5(2s+2m)= | | -111=-3(1+6n) | | 50+5x=15+12x | | 12x-5=4x-1 | | 7x+11=7+7x | | -2(-4+y)-5y=15 | | -13+4b=-3b-7 | | 4x-3+2x+53=90 | | y=5x^2+2x-1 | | -3(g-9)+-9=-9 | | 4x-3+2x+53=180 | | 3x+x-2=-x+7 | | 2(p-4)-3=9 | | 5x+5(2x+11)=160 | | 2=k+2+5k | | 12+-5=x |